2019
DOI: 10.1002/bit.27163
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐facilitated gold nanoparticle formation as indicators of ionizing radiation

Abstract: The use of X-ray radiation in radiotherapy is a common treatment for many cancers.Despite several scientific advances, determination of radiation delivered to the patient remains a challenge due to the inherent limitations of existing dosimeters including fabrication and operation. Here, we describe a colorimetric nanosensor that exhibits unique changes in color as a function of therapeutically relevant radiation dose (3-15 Gy). The nanosensor is formulated using a gold salt and maltose-binding protein as a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…The structure from the resulting crystals was subsequently determined to a resolution of 1.95 Å (Table S1), suggesting that the crystals would be suitable for studies with HAuCl 4 . Additionally, the all-atom RMSD between the tetragonal crystal form of MBP at low pH compared with a previously solved MBP structure from a monoclinic crystal form grown at higher pH of 6.2 (Quiocho et al, 1997) was 0.776 Å, indicating that the lower pH does not significantly alter the structure of MBP, which is in agreement with previous work (Thaker et al, 2019). For experiments in the presence of gold, the MBP crystals were harvested and soaked in precipitant solution supplemented with 10 mM HAuCl 4 and 10% glycerol, and cryo-cooled by plunging into a liquid nitrogen bath before data collection.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The structure from the resulting crystals was subsequently determined to a resolution of 1.95 Å (Table S1), suggesting that the crystals would be suitable for studies with HAuCl 4 . Additionally, the all-atom RMSD between the tetragonal crystal form of MBP at low pH compared with a previously solved MBP structure from a monoclinic crystal form grown at higher pH of 6.2 (Quiocho et al, 1997) was 0.776 Å, indicating that the lower pH does not significantly alter the structure of MBP, which is in agreement with previous work (Thaker et al, 2019). For experiments in the presence of gold, the MBP crystals were harvested and soaked in precipitant solution supplemented with 10 mM HAuCl 4 and 10% glycerol, and cryo-cooled by plunging into a liquid nitrogen bath before data collection.…”
Section: Resultssupporting
confidence: 90%
“…The results of MBP facilitated gold nanoparticle synthesis are in agreement with other studies on protein‐aided nanoparticle synthesis. The effect of pH when using MBP with HAuCl 4 and HEPES, that is, lower pH enabling AuNP synthesis as described here and higher pH inhibiting AuNP synthesis that was described previously (Thaker et al, 2019), has also been reported for other AuNP systems with peptides and proteins (Shimojo et al, 2012). This further suggests that when using biomolecules for inorganic nanoparticle synthesis and stability, a range of pH should be investigated because varying results can be obtained using the same precursors.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Nanotechnology-enabled sensors provide new solutions for the detection of ionizing radiation with increased selectivity and sensitivity . We have pioneered the development of a colorimetric sensor wherein ionizing radiation facilitates the generation of gold nanoparticles from their colorless ionic precursor solutions in liquid or gel formulations. Here, for the first time, we demonstrate the adoption of this colorimetric radiation-responsive gel nanosensor technology toward multiple clinically relevant applications, including brachytherapy, by using them for dose detection in three distinct form factors: linear (1D), area (2D), and volumetric (3D) morphologies. We also demonstrate the use of distinct quantitative readout methods, including visual/optical and photothermal detection, which further augments the versatility of gel nanosensors.…”
Section: Introductionmentioning
confidence: 98%